2018
DOI: 10.18203/2394-6040.ijcmph20183984
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy and its outcomes: a cross-sectional study

Abstract: Background: Teenage or adolescent pregnancy is a major public health problem worldwide. Studies show that teenage mothers are more likely to experience pregnancy-related complications and maternal death compared to adult mothers. Hence, this study was conducted to study the socio-demographic profile and the maternal and fetal outcomes associated with teenage pregnancy and compare it with those of mothers aged 20-30 years.Methods: A cross-sectional comparative study was conducted in Government General Hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 6 publications
(16 reference statements)
2
15
0
3
Order By: Relevance
“…Another factor that enables severe maternal morbidity is gestational hemorrhagic syndromes, which are preventable with proper treatment. The study by Paladugu RK and colleagues found that PMR and APH were significantly higher in adolescent mothers compared with adult mothers (20% vs. 4%, p <0.05; 20% vs. 4%, p < 0.05, respectively) [13], similar results were observed in other studies by Yasmin et al in Madhya Pradesh and Talawar et al in India [14,15].…”
Section: Discussionsupporting
confidence: 82%
“…Another factor that enables severe maternal morbidity is gestational hemorrhagic syndromes, which are preventable with proper treatment. The study by Paladugu RK and colleagues found that PMR and APH were significantly higher in adolescent mothers compared with adult mothers (20% vs. 4%, p <0.05; 20% vs. 4%, p < 0.05, respectively) [13], similar results were observed in other studies by Yasmin et al in Madhya Pradesh and Talawar et al in India [14,15].…”
Section: Discussionsupporting
confidence: 82%
“…Whereas, a multi country study carried out by WHO found a lower risk of pre-eclampsia among adolescent compared to adult women [84]. Similarly, studies conducted in Ontario [93], and South Glamorgan region of Wales [94], and India [95] also showed a significantly lower risk of PIH among adolescent than adult women. These controversial findings may be due to the difference in the age-related reference and failure to adjust confounding variables in the different studies.…”
Section: Plos Onementioning
confidence: 93%
“…Many studies indicate that complications increase in prevalence and magnitude in adolescent pregnant women, which may contribute towards an increased risk of adverse maternal/neonatal events. [1][2][3][4] The present study aimed to investigate obstetric complications in adolescents that were attended by MECS.…”
Section: Pregnancy Complications; Pregnancy In Adolescentsmentioning
confidence: 99%